2011
DOI: 10.1007/s12016-011-8294-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mimicry as a Mechanism of Autoimmune Disease

Abstract: A variety of mechanisms have been suggested as the means by which infections can initiate and/or exacerbate autoimmune diseases. One mechanism is molecular mimicry, where a foreign antigen shares sequence or structural similarities with self-antigens. Molecular mimicry has typically been characterized on an antibody or T cell level. However, structural relatedness between pathogen and self does not account for T cell activation in a number of autoimmune diseases. A proposed mechanism that could have been misin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
298
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(310 citation statements)
references
References 137 publications
4
298
1
7
Order By: Relevance
“…that vimentin resembles the molecular structure of a microbial antigen ( possibly mKatG) and reactive T-cells might cross-react to a vimentin self antigen. In fact, molecular mimicry indeed plays a role in several autoimmune or autoaggressive diseases [20]. Thus, the work presented here might give an explanation why we do see reactivity against bacterial antigens despite the fact that these microorganisms are no longer present.…”
mentioning
confidence: 57%
“…that vimentin resembles the molecular structure of a microbial antigen ( possibly mKatG) and reactive T-cells might cross-react to a vimentin self antigen. In fact, molecular mimicry indeed plays a role in several autoimmune or autoaggressive diseases [20]. Thus, the work presented here might give an explanation why we do see reactivity against bacterial antigens despite the fact that these microorganisms are no longer present.…”
mentioning
confidence: 57%
“…Human commensal pathogens that have established a pattern of 'hit and stay' (such as herpes simplex virus) have more redundant sequences than pathogens that 'hit and run' (such as Ebola and Marburg) [17,18]. To what degree this redundancy may contribute to autoimmunity, is as yet unknown [19].…”
Section: Tcr Degeneracy Epitope Redundancy Mimicry and Camouflagementioning
confidence: 99%
“…24,25 Viral myocarditis, Lyme disease, rheumatoid arthritis, multiple sclerosis, and virus-induced autoimmune diabetes are autoimmune diseases that are considered to be initiated or aggravated by immune challenge with microbial pathogens. [24][25][26][27][28] Consistent with this model, we have previously shown that a MAGE-A6-derived peptide, MAGE-A6 172-187 , and a peptide derived from the permease protein of the ubiquitous Mycoplasma penetrans HF-2 bacterium (HF-2 216-229 ) share a high-degree of structural homology and immunologic cross-reactivity in the CD4 C T-cell compartment present in a broad range of healthy donors and melanoma patients. 29 We now show that these same MAGE-A6 172-187 and HF-2 216-229 peptides can induce a cross-reactive, polyclonal CD8 C T-cell repertoire in HLA-A*0201 (HLA-A2)…”
Section: Introductionmentioning
confidence: 99%